2010
DOI: 10.1159/000322656
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Breast Carcinoma Presenting as Perforated Appendicitis

Abstract: Background: Patients presenting with symptoms from unknown metastatic breast carcinoma are becoming increasingly uncommon. Perforated appendicitis from metastatic breast carcinoma is a rare entity with only a few published reports in the literature. Case Report: The case of a 76-year-old female patient who developed perforated appendicitis from previously unknown metastatic breast cancer is presented. During physical examination in the emergency department, a large left breast mass was palpated. The patient un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…Breast cancer metastasizing to the appendix is also a rare occurrence [ 23 ] and there are very few published reports of MBC presenting as appendicitis [ 29 31 ]. McLemore et al [ 13 ] reported that 21% of patients presented with metastatic disease masquerading as an alternate disease process, thus making accurate diagnosis difficult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Breast cancer metastasizing to the appendix is also a rare occurrence [ 23 ] and there are very few published reports of MBC presenting as appendicitis [ 29 31 ]. McLemore et al [ 13 ] reported that 21% of patients presented with metastatic disease masquerading as an alternate disease process, thus making accurate diagnosis difficult.…”
Section: Discussionmentioning
confidence: 99%
“…There were no histological features of appendicitis in the case described; however, the lumen of the appendix contained metastatic tumour deposits. Dirksen et al [ 31 ] have suggested that metastatic adenocarcinoma to the appendix can often present as appendicitis at a late stage leading to a high incidence of perforation. Chemotherapy and endocrine therapy, often in combination, is the treatment of choice in these patients.…”
Section: Discussionmentioning
confidence: 99%
“… 1 The primary sites of metastatic appendiceal carcinomas were the lung, breast, cervix, prostate, stomach, liver, nasopharynx, mediastinum, and pancreas. 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 As far as we know, primary cholangiocellular carcinoma very rarely metastasizes to the appendix. 14…”
Section: Discussionmentioning
confidence: 99%
“…Without imaging studies for patients with suspected appendicitis, it is very difficult to diagnose primary or metastatic carcinoma of the appendix. 2 , 6 , 7 , 8 , 9 , 10 , 11 As imaging modalities are more frequently used, appendiceal masses are found before surgery more commonly, sometimes with unusual characteristics. 3 , 4 , 5 , 13 In a recent report of a case of appendiceal metastasis from a hepatocellular carcinoma, CT scan was useful in the diagnosis of the metastatic lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Extrahepatic GI tract metastasis involves more often the stomach and the small intestine and, very rarely, the colon and rectum [ 6 ]. Other rare metastatic sites include the appendix [ 7 ], endometrium [ 8 ], gallbladder [ 9 ], kidney [ 10 ], orbit [ 11 ], pancreas [ 12 ], parotid gland [ 13 ], spleen [ 14 ], urinary bladder [ 15 ], uterine cervix [ 8 ], uterus [ 16 ], and vulva [ 17 ].…”
Section: Introductionmentioning
confidence: 99%